A widely conserved bacterial cell division protein that promotes assembly of the tubulin-like protein FtsZ - Gueiros-Filho, Frederico J. (Cold Spring Harbor Laboratory Press, 2002)
Cell division in bacteria is mediated by the tubulin-like protein FtsZ, which assembles into a structure known as the Z ring at the future site of cytokinesis. We report the discovery of a Z-ring-associated protein in Bacillus subtilis called ZapA. ZapA was found to colocalize with the Z ring in vivo and was capable of binding to FtsZ and stimulating the formation of higher-order assemblies of the cytokinetic protein in vitro. The absence of ZapA alone did not impair cell viability, but the absence of ZapA in combination with the absence of a second, dispensable division protein EzrA caused a severe block in cytokinesis. The absence of ZapA also caused lethality in cells producing lower than normal levels of FtsZ or lacking the division-site-selection protein DivIVA. Conversely, overproduction of ZapA reversed the toxicity of excess levels of the division inhibitor MinD. In toto, the evidence indicates that ZapA is part of the cytokinetic machinery of the cell and acts by promoting Z-ring formation. Finally, ZapA is widely conserved among bacteria with apparent orthologs in many species, including Escherichia coli, in which the orthologous protein exhibited a strikingly similar pattern of subcellular localization to that of ZapA. Members of the ZapA family of proteins are likely to be a common feature of the cytokinetic machinery in bacteria.